Analysis of Epstein-Barr virus infection models in a series of pediatric carriers from a developing country - Vistarop, Aldana Georgina (2016)
Epstein-Barr virus (EBV) is a B lymphotropic human herpesvirus. Two models, germinal center (GC)and direct infection, describe how EBV infects B-cells. Since in Argentina primary infection is mostly subclinical at young ages, children represent an interesting population where to analyze EBV infection, especially considering that most studies are usually performed in adults. Tonsil biopsies from pediatriccarriers were studied to describe infection characteristics. EBV+ lymphocytes at the interfollicular region were mainly observed. Latency III pattern in subepithelial (SubEp) lymphocytes was observed at young ages, probably indicating a recent infection. In older patients EBV was mostly detected in epithelial cells, suggesting that they could have been infected some time ago. This finding was sustained by tonsillar viral load, which was higher in cases with LMP1+SubEp cells vs. LMP1+nonSubEp cells (p = 0.0237, Mann-Whiney test). Latency III was prevalent and related to the GC, while latency II was associated with non-GC (p = 0.0159, χ2 test). EBERs+/IgD+ cells were statistically prevalent over EBERs+/CD27+ cells (p = 0.0021, χ2 test). These findings indicated that both EBV infection models arenot mutually exclusive and provide some basis for further understanding of EBV infection dynamics. Moreover, we provide a more accurate explanation of EBV infection in pediatric asymptomatic carriers from a developing country.